Bilateral Proximal Femur Interval Fractures with a Slipped Femoral Capital Epiphysis After Fixation: A Case Report. - Boughton,OR; Mann,S; O'Toole,P (JBJS Case Connect, 2025)
CASE: This case report, with 3 years of follow-up, describes a 9-year-old boy who suffered sequential Delbet type IV proximal femoral fractures. Three months postoperatively he had a unilateral slipped capital femoral epiphysis and had to undergo further surgery to address this. CONCLUSION: Proximal femur fractures are rare in childhood, and a slipped capital femoral epiphysis after fixation of a Delbet type 4 fracture has only been described once before in the literature. This case report highlights underlying risk factors of subsequent slipped capital femoral epiphysis after a Delbet type IV proximal femoral fracture and emphasizes the importance of careful follow-up.